2022
DOI: 10.1097/01.hjh.0000835536.47640.cf
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal Vessel Diameter Are Associated With Cerebral Microbleeds in Neurologically Asymptomatic Individuals With Type 1 Diabetes

Abstract: Objective:We observed recently that a third of asymptomatic individuals with type 1 diabetes (T1D) showed signs of cerebral small-vessel disease in brain magnetic resonance imaging (MRI). Here, we aimed to explore the relationship between an easily applicable quantitative measure of retinal vessel diameters (RVD) and cerebrovascular changes in these individuals.Design and method:We included 188 individuals with type 1 diabetes and 30 healthy sex and age matched (49% males, median age 40 years) controls. Any ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Tarkkonen et al reported that central retinal arteriolar equivalent was lower in patients with more than 10 CMBs than in those without [ 28 ]. The current study found that the presence of CMBs and enlarged perivascular spaces was independently related with the decrease of OA diameter, thus suggesting that the OA diameter may reflect the presence of MRI signs of CSVD.…”
Section: Discussionmentioning
confidence: 99%
“…Tarkkonen et al reported that central retinal arteriolar equivalent was lower in patients with more than 10 CMBs than in those without [ 28 ]. The current study found that the presence of CMBs and enlarged perivascular spaces was independently related with the decrease of OA diameter, thus suggesting that the OA diameter may reflect the presence of MRI signs of CSVD.…”
Section: Discussionmentioning
confidence: 99%